Espectros de gotas e taxas de aplicação de fungicidas em diferentes horários no controle da ferrugem asiática da soja - Cadore, Pedro Ceretta (2017)
Asian rust causes significant yield loss in soybean and its control is based on fungicide applications. Factors related to application technology, such as techniques adopted and climatic conditions, influence the success of disease control. The aim of this study was to evaluate the fungicide applications at different times through different droplets spectra and application rates, aiming at maximum control efficiency of Asian soybean rust. The experiment was conducted in two seasons in randomized complete block design in fatorial scheme (5 x 2 x 3) + 1 with split-plot arrangement and four replications. The factors studied were five application times (5 a.m. 9 a.m. and 1 p.m., 5 p.m., 9 p.m.), two droplets spectra (fine and medium), three application rates (60, 100 and 140 L.ha-1) and a control treatment (no application). Four applications were performed, the first three with the fungicide Trifloxystrobin + Protioconazole (60 + 70 g.a.i.ha-1) and the last with the fungicide Trifloxystrobin + Ciproconazole (75 + 32 g.a.i.ha-1). All fungicide treatments received the addition of Aureo® (0.25% v.v-1). The variables evaluated were Volumetric Medium Diameter (VMD), droplets density, leaf area covered by drops, Area Under the Rust Progression Curve (AURPC), Normalized Difference Vegetation Index (NDVI) and soybean yield. The results showed that: the fine spectrum promoted greater penetration and droplets coverage in the crop canopy; the increase in application rate increased droplets coverage, disease control, and crop yield; the application times at 9 a.m., in the first season, and at 5 p.m., in the second season, showed the best effective control of Asian soybean rust.